2009
DOI: 10.1002/chem.200802520
|View full text |Cite
|
Sign up to set email alerts
|

Ligand Selection in RuII Complexes for Direct One‐Electron Photooxidation of Guanine: A Combined Computational and Experimental Study

Abstract: Making the right ligand selection: DFT calculations of Gibbs energies for the one-electron photooxidation of guanine by six Ru(II)-polypyridine complexes are reported. The theoretical predictions are compared with new EPR spectra. Our theoretical calculations confirm the experimental observations that the direct photooxidation of guanine by [Ru(bpz)(3)](2+), [Ru(tap)(3)](2+), and [Ru(bpz)(2)(dppz)](2+) is thermodynamically favorable, but is unfavorable with [Ru(bpy)(3)](2+), [Ru(phen)(3)](2+), and [Ru(bpy)(2)(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Ru͑bpy͒ 3 2+ is not a good example for such electron transfer but other ligands such as 2,2Ј-bipyrazine or dipyrido͓3,2-a :2Ј ,3Ј-c͔phenazine are, as we have shown in a recent paper. 35 The emission spectra from both the D 3 and C 2 MLCT states have been calculated and again, at least for the D 3 MLCT state, the spectra reproduce quite well the experimental data. However, we have shown that it will be very difficult to differentiate the emission from these two states ͑D 3 versus C 2 MLCT͒.…”
Section: Discussionmentioning
confidence: 61%
“…Ru͑bpy͒ 3 2+ is not a good example for such electron transfer but other ligands such as 2,2Ј-bipyrazine or dipyrido͓3,2-a :2Ј ,3Ј-c͔phenazine are, as we have shown in a recent paper. 35 The emission spectra from both the D 3 and C 2 MLCT states have been calculated and again, at least for the D 3 MLCT state, the spectra reproduce quite well the experimental data. However, we have shown that it will be very difficult to differentiate the emission from these two states ͑D 3 versus C 2 MLCT͒.…”
Section: Discussionmentioning
confidence: 61%
“…Moreover, we have shown that the energy level of the singlet and triplet MLCT states can be tuned by the use of the dab ligand. This ligand can therefore be useful to adjust the energy of the excited state populated after photoabsorption of ruthenium(II) complexes opening new perspectives for photoinduced electron transfer applications. ,, …”
Section: Resultsmentioning
confidence: 99%
“…As a first step, the geometries of the ground state of the low-spin Ru(II) (4d 6 valence configuration) complexes were optimized in vacuo using the B3LYP functional. , The 6-31G* basis set , was used for the C, N, and H atoms while the “Stuttgart RSC 1997 ECP” relativistic effective core potential and associated basis set was employed to describe the Ru atom. This potential has been shown to allow an accurate description of the electronic and bonding properties of Ru complexes. The structures obtained for the [Ru(tap) 3 ] •+ and [Ru(tap) 2 (phen)] •+ complexes display a D 3 and C 2 symmetry, respectively. By performing geometry optimizations in the C 1 symmetry group, we verified that we obtained a higher total energy for both systems.…”
Section: Methodsmentioning
confidence: 99%